MAKNA TEKS MEUDIKEE ANGGOK DILIHAT DARI KONSEP BILDUNG DAN SENSUS COMMUNIS MENURUT GADAMER DI DAYAH DARUL HUDA DESA BAYI KECAMATAN TANAH LUAS KABUPATEN ACEH UTARA - Putri Kusuma; Dilinar Adlin (Gesture: Jurnal Seni Tari, 2018)
ABSTRACT This study discusses the meaning of the text meudikee anggok seen from the concept bildung and sensus communis gadamer. Aims to describe the meaning of meudikee anggoktext of wisdom seen from the concept of bildung and sensus communis according to gadamer. Theories used are text theory and hermeneutics. Hermeneutics is a theory used to interpret. Seen from the concept of bildung is the form and sensus communis namely the true feeling and common good in society as the owner of the ritual.  The time of the research was conducted in july until the mont of september 2017. Place of research in infant village, sub district wide area of nort Aceh regency. Population of artists, public figures and children dzikir which amounted to 180. The research sample is a child dzikir 20 people. Leadershipand tengku amounted to 2 people and geuchik baby village so that the sample amounted to 23 people. Data collection techniques include observation, interview, literature study, documentation and then analyzed by qualitative descriptive method. Based on reasearch that has been done meaning meudikee text seen from the concept of bildung and sensus communis. On the concept of bildung in the form of motion, chanting dzikir and clothing. On the sensus communis concept of community agreement the meaning contained in the motion of whether to surrender, plead, salute, appreciate, sincere, passion, agree, protect, tought ad ask. The meaning contained in chanting dzikir is honor, glorify, pray, begged, apologize, sacrifice, struggle, love, loyalty, ask for blessings and hope. The meaning contained in clothing is clean, holy, strength, death, firmness, decency, cover of aurat. Where the text contained in the concept of the sensus communis can be seen from the deliberation in planning the implementation of activities that contain the meaning of cooperation, cohesivenees and respect. People work together to prepare meunasah and food to be brought to the meunasah. As for its meaning is sincare, give each other, mutual cooperation, happy, spirit and joy. Keyword : Meudikee Anggok, Village baby, Bildung, Sensus Communis.